2011
DOI: 10.1007/s12187-011-9110-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Exposed to 7 Years of Political Violence: Differential Relations Between Exposure and Its Impact for Jewish and Arab Israelis

Abstract: The first aim of this study was to describe exposure to political violence and its assigned impact for Israeli adolescents growing up in the Israeli-Palestinian conflict environment, spanning 7 years of the second Palestinian Intifada (1998)(1999)(2000)(2001)(2002)(2003)(2004). The second aim was to examine ethnic group differences in exposure and impact over this period. Participants were 3800 Jewish and Arab Israeli adolescents, sampled in a cross-sectional design during three exposure periods-antecedent, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Several studies have revealed that exposure to previous traumatic war experiences and events is a risk factor for the development of post-traumatic stress disorder (PTSD), grief, and depression (21,22). The exposure to traumatic events, specifically physical injuries, loss of loved ones, immediate risk of life (2,23), injury of a family member or friend (2,(24)(25)(26) and losing a family member (27) are the strongest risk factors for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that exposure to previous traumatic war experiences and events is a risk factor for the development of post-traumatic stress disorder (PTSD), grief, and depression (21,22). The exposure to traumatic events, specifically physical injuries, loss of loved ones, immediate risk of life (2,23), injury of a family member or friend (2,(24)(25)(26) and losing a family member (27) are the strongest risk factors for PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Children who are exposed to war-traumatic events are likely to develop cognitive, emotional and behavioural dysfunction symptoms (Khamis, 2015;Myers-Walls, 2004;Shaw, 2003), as well as a sense of insecurity, which may lead to physical health problems (Ursano, 2002). One recurrent disorder related to exposure to war-traumatic events is PTSD (Slone & Shechner, 2011;Smith et al, 2001;Kolltveit et al, 2012, Wayment, 2004Hasanovic et al, 2006;De Jong et al, 2001). According to American Psychiatric Association (2013), PTSD refers to a psychiatric disorder includes intrusion symptoms, avoidance, negative alterations in cognitions and mood, and alterations in arousal and reactivity that can occur in people who have experienced or a traumatic.…”
Section: Introductionmentioning
confidence: 99%
“…(p. 541) In considering the findings of their study, Slone and Shechner (2011) emphasized the Israeli Arab adolescents' 'torn position' regarding a dual loyalty to historical Palestinian affiliation and current Israeli citizenship. From a differential vantage point, they noted that Jewish adolescents were more exposed to eroding daily insecurity and tension, victimization in terrorist attacks, and losses from family members' involvement in military activity, whereas Arab adolescents were more exposed to involvement in violent demonstrations and destruction of property.…”
Section: Differential Exposure Effect: Israeli-arab and Jewish Israelmentioning
confidence: 98%
“…Slone and Shechner (2011), for instance, investigated the differential effects of political violence on Arab and Jewish Israeli youth. Israelis-Arab make up 20.3% of the total Israeli population (Central Bureau of Statistics, October, 2010, cited in Slone and Shechner 2011), and have been exposed to this violence as well.…”
Section: Self-efficacy Among Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation